Comparative Assessment of Nutraceuticals for Supporting Skin Health - Meike Streker; Ehrhardt Proksch; Jan-Christoph Kattenstroth; Burkhard Poeggeler; Gunter Lemmnitz (Nutraceuticals)
Background/Objectives: The term “nutraceuticals” refers to food and dietary supplements promoted for their health benefits in addition to their nutritional value. These products contain plant- or animal-derived nutrients, vitamins, minerals, trace elements, and similar compounds aimed at enhancing skin health and influencing visible skin quality. This review provides an overview of the current research on nutraceuticals and the scientific evidence supporting their effects on skin health. Methods: The literature on more than 50 selected nutraceuticals was examined to assess any clinically substantiated, beneficial effects on skin health. The assessment was based on scientific evidence, including the quality and quantity of empirically gathered and evaluated findings. Results: A total of 17 common dietary supplements, either as individual compounds or categorized into groups, along with some combination products, were identified as nutraceuticals with well-supported effects on skin health. These include, among others, vitamins A, B7, C, and E; collagen peptides; carotenoids; and various plant extracts. For many other nutraceuticals, clinical evidence for their effects on skin health is limited or insufficient. Conclusions: The literature indicates that many nutraceuticals marketed for skin health are more or less suitable for this application based on the evidence assessment.